The cognitive psychology of moral reasoning - Gubbins, Eoin (Trinity College (Dublin, Ireland). School of Psychology, 2014)
In this thesis, the results of eight experiments are presented investigating he cognitive processes involved in moral reasoning. Two major themes were explored, involving important contemporary debates in moral psychological research. The first of these themes was the role of domain-general cognitive processes in moral judgment. The second was the role of emotions as information in moral reasoning. These issues were explored over the course of three experimental series.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin